PENGARUH LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK SOSIODRAMA TERHADAP PENINGKATAN KEDISIPLINAN SISWA KELAS VIII - Imas Nurjanah; Euis Eti Rohaeti; Tuti Alawiyah (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
The goal to be achieved in this study is group guidance services with sociodrama techniques to improve the discipline of class VIII students. The approach in this study uses quantitative research with experimental methods. The design used in this study was pre-experimental with the type of one group Pre-test and post-test design. This study used 7 subjects in class VIII SMP Negeri 1 Cipatat T.A 2020/2021. The type of instrument used is a student discipline questionnaire. The results of the study on the final pretest score showed a score of 519 with a percentage value of 62%. While the posttest results showed a final score of 717 with a percentage value of 85%, thus an increase in students after being given treatment. The results of the calculation of the normality test using SPSS 20.0 for windows using a pretest value of 0.200 and a posttest value of 0.200. So it can be shown that the significant value of the pretest is 0.200 0.05 and the posttest is 0.200> 0.05. So it can be concluded that the data is normally distributed (effective). Thus the working hypothesis (Ha) is accepted which reads "Group Guidance Services with Effective Sociodrama Techniques, Due to the Positive and Significant Influence on Improving Discipline of Class VIII Students at SMP Negeri 1 Cipatat for the 2020/2021 Academic Year". Keywords:Group Guidance Services, Sociodrama Techniques, Student Discipline.